Evaluasi Pemilihan Supplier Kemasan So Klin Terbaik Menggunakan Analytical Hierarchy Process di PT Sayap Mas Utama - Catur Medilasito; Jasan Supratman (Department of Petroleum Engineering, 2022)
PT Sayap Mas Utama is a company engaged in the toiletry industry. The products produced include DAIA detergent, So Klin detergent, Economy cream soap, Blue Wings cream soap and Dang Dut cream soap. The packaging used to pack these products is plastic / cellophane roll. In its production, PT Sayap Mas Utama cooperates with several cellophane suppliers, namely Unipack, Bonavista, Toppan, and Iluva. It is required because if only work with one supplier, the production needs for packaging cannot be fulfilled. This is happened due to the productivity level of PT Sayap Mas Utama is indeed quite high. There are some suppliers has differences in the delivery of goods so that this influence to the productivity of the company. By this research, it is expected that the company can find the best supplier by considering several criteria, namely price, quality, service, delivery accuracy, and quantity suitability. After conducting research using the Analytical Hierarchy Process (AHP) method with the help of the Expert choice application, it was found that Unipack is the best supplier with a weight value of 0.311. Next is Toppan with a weight value of 0.276, Bonavista with a weight value of 0.241 and Iluva with a weight value of 0.158. Reference: Bourgeois, R. (2005). Analytical Hierarchy Process. Bogor: UNCAPSA-UNESCAP. Hanugrani, N., Setyanto, N. W., & Efanto, R. Y. (2014). Pengukuran Performansi Supply Chain dengan Menggunakan Supply Chain Operation Reference (SCOR) berbasis Analitycal Hierarchy Process (AHP) dan Objective Matrix (OMAX). Hasdi, R. F., Sudarmaningtyas, P., & Supriyanto, A. (2014). Rancang Bangun Sistem Pendukung Keputusan Pemilihan Supplier dengan Metode AHP. Laksmi, Fuad, & Budiantoro. (2008). Manajemen Perkantoran Modern. Jakarta: Pernaka. Putri, C. F. (2012). Pemilihan Supplier Bahan Baku Pengemas Dengan Metode AHP (Analitycal Hierarchy Process). Sari, D. P., & Kusumo, S. A. (2011). Evaluasi Pemilihan Supplier Terbaik Menggunakan Metode Taguchi Loss Functions dan Analytical Hierarchy Process di PT Indomaju Textindo Kudus. Sudri, N. M., Nendisa, B. C., & Wibisono, S. (2014). Perancangan Vendor Appraisal dengan Metode Fuzzy Analytical Hierarchy Process di PT XYZ. Surjasa, D., Astuti, P., & Nugroho, H. (2005). Usulan Selection dengan Analytical Hierarchy Process dan Penenrapan Sistim Informasi dengan Konsep Vendor Managed Inventory pada PT ABC. Jakarta: Universitas Trisakti. Viarani, S. O., & Zadry, H. R. (2015). Analisis Pemilihan Pemasok dengan Metode Analitycal Hierarchy Process di Proyek Indarung VI PT Semen Padang. Wulandari, N. (t.thn.). Perancangan Sistem Pendukung Keputusan Pemilihan Supplier di PT Alfindo dengan Metode Analytical Hierarchy Process (AHP). Wulandari Ratri (2015). Pemilihan Supplier Bahan Baku Partikel Dengan Metode AHP Dan Promethee Yulianto Joko (2017). Pemilihan Alat Pancang Menggunakan Expert Choice